Macromol. React. Eng. 3/2022. Issue 3 (16th June 2022) - Unknown
Abstract : Front Cover : Carboxylated cellulose nanocrystals (cCNCs) are used to enhance latex‐based pressure‐sensitive adhesive (PSA) properties. AFM imaging reveals that cCNCs interact with latex particles and each other; thus, omitting ultrasonication at the preparation stage preserves these interactions and leads to greater property enhancements. The research demonstrates how cCNCs provide superior, fibril‐like reinforcements to PSA films without the technical challenges associated with producing composites with nanofibrils. This is reported by Marc A. Dubé and co‐workers in article number 2100051 .